Stimulating Students` Vocabulary and Grammar in Speaking Using Audio-Video and Picture - Febria, Herdinatara; Ifadah, Muhimatul; Aimah, Siti (English Language and Literature International Conference (ELLiC) Proceedings, 2017)
The difficulty of junior school students in expressing ideas, thoughts, opinions, or feelings into spoken language, is the background of the study. The objective of the study are to find out whether there is significant achievement on students speaking taught using audio-video and picture, and to describe the significant difference of speaking components between the students taught using audio-video and picture. By applying quantitative approach through experimental study, 60 students of grade VIII SMP Muhammadiyah 03 Semarang were taken as the sample. To get qualitative data, questionnaire was delivered for those students. The result of the study showed that from five aspects in speaking assessment; pronoun, grammar, vocabulary, fluency, and comprehension, the increasing of vocabulary and grammar showed the highest level, followed by comprehension. Meanwhile, the students fluency in speaking did not provide significant enhancement, only 0.4 percent. From the questionnaire, the students delivered that their enthusiasm was positively supported by the use of media; however, the media was also aside their boredom in the learning process. From the study, it was suggested to the teacher to find appropriate theme and topic, related to the students age to help students learning in comfort way.